2022
DOI: 10.5811/westjem.2022.7.56501
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Ultrasound-guided Central Venous Catheter Confirmation vs Chest Radiography in Critically Ill Patients: A Labor Cost Model

Abstract: Introduction: Despite evidence suggesting that point-of-care ultrasound (POCUS) is faster and non-inferior for confirming position and excluding pneumothorax after central venous catheter (CVC) placement compared to traditional radiography, millions of chest radiographs (CXR) are performed annually for this purpose. Whether the use of POCUS results in cost savings compared to CXR is less clear but could represent a relative advantage in implementation efforts. Our objective in this study was to evaluate the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our search identified and screened 4071 articles, of which 117 full-text articles were accessed for eligibility (Figure 1). 3,611,13,14,1720,2957 We retained 41 articles based on prespecified criteria for inclusion (Table 1). Regarding ultrasound guided placement and confirmation methods, 13 articles examined cardiac/vascular methods; 5 examined isolated contrast-enhanced ultrasonography (CEUS); 7 examined isolated rapid atrial swirl sign (RASS); and 13 examined combined/integrated methods (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified and screened 4071 articles, of which 117 full-text articles were accessed for eligibility (Figure 1). 3,611,13,14,1720,2957 We retained 41 articles based on prespecified criteria for inclusion (Table 1). Regarding ultrasound guided placement and confirmation methods, 13 articles examined cardiac/vascular methods; 5 examined isolated contrast-enhanced ultrasonography (CEUS); 7 examined isolated rapid atrial swirl sign (RASS); and 13 examined combined/integrated methods (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We would like to commend Dr. Ablordeppey and her colleagues for their recent publication in the Western Journal of Emergency Medicine evaluating the comparative labor cost of central venous catheter confirmation via point-of-care ultrasound (POCUS) vs traditional chest radiography (CXR). 1 To our knowledge, this well-designed article was the first to analyze in detail the direct labor cost of using POCUS-guided confirmation for central lines vs traditional CXR confirmation. We were surprised when the authors reported that the POCUS-guided method was only $3.82 cheaper than the CXR method.…”
mentioning
confidence: 99%
“…We would like to thank Austin et al 1 for their interest in our article comparing labor costs of two approaches to central venous catheter (CVC) confirmation, 2 recently published in the Western Journal of Emergency Medicine . In their letter to the editor, they acknowledge that the point-of-care ultrasound (POCUS)-guided confirmation method offers direct and potential indirect cost benefits when compared with the chest radiograph (CXR) method.…”
mentioning
confidence: 99%